KETERKAITAN KEBIASAAN MAHASISWA MENGGUNAKAN MOBIL KE KAMPUS DENGAN KARAKTERISTIK DEMOGRAFI, EKONOMI, DAN PERJALANAN MAHASISWA KE KAMPUS - Setiawan, Rudy; Santosa, Wimpy; Sjafrudin, Ade (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The most common daily trip for university students is the commuting to campus. Though there are clear environmental, economic, and social drawback from using private vehicles for these trips, students still choose private vehicles to get to campus. This study discusses the correspondence between students' car use habit with a variety of demographic, economic, and trip characteristics. This research is expected to provide benefits in the design of campus transportation policies to reduce trips to the campus by car. Results of the analysis indicate that there are associations between the habit of using a car to campus with students gender and city of residence. In addition, there is a significant relation between the students' car use habit with campus, years of study, the distance from residence, residence status, car ownership, frequency of trips to the campus per day, car accessibility, and car usage behavior in the previous semester.